Highly Sensitive Electrospun Multiwalled Carbon Nanotubes Embedded Zinc Oxide Nanowire Based Interface for Label Free Biosensing. (2017) - Paul, K. Brince; Vanjari, Siva Rama Krishna; Singh, Shiv Govind
Abstract: We demonstrate synthesis of Multiwalled carbon nanotubes (MWCNTs) embedded highly oriented Zinc Oxide (ZnO) nanowires targeted towards development of ultrasensitive electrochemical nanobiosensors using electrospinning method. The synthesized composite nanowires combines advantages of ZnO such as biocompatibility, electrostatic affinity towards biomolecules with the excellent conductivity and surface functionalization capabilities of MWCNTs. Calcination temperature is optimized so as to ensure MWCNTs are present in their original form and at the same time highly crystalline ZnO is obtained. The key advantage of this process is that there is no separate functionalization process is required to create functional groups on MWCNTs. Furthermore, the electrochemical activity of MWCNTs embedded ZnO nanowires is much higher as compared to pure ZnO nanowires. We have demonstrated the performance of electrochemical nanobiosensor using Biotin-streptavidin interaction as model system. The sensor exhibits excellent sensitivity in the range 10 μgmL -1 - 0.5 fgmL -1 of streptavidin with 0.5fgmL -1 limit of detection.